2007
DOI: 10.1007/s00168-007-0143-5
|View full text |Cite
|
Sign up to set email alerts
|

Modelling dynamics of knowledge networks and local connectedness: a case study of urban high-tech companies in The Netherlands

Abstract: There are increasing doubts on the importance of localized knowledge and learning as benefits from a clustered location. Some empirical studies indicate that the influence of local proximity in knowledge networks stretches over larger distances than in previous times, while others suggest that local and global knowledge networks coexist. This study seeks to fill a gap in understanding how knowledge networks are shaped and how global networks may affect strength of local connectedness in a cluster. The study ad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(9 citation statements)
references
References 70 publications
(50 reference statements)
1
7
0
1
Order By: Relevance
“…Therefore, it is argued that successful innovation is based on the appropriation of specialized regional know-how, on the one hand, and globally dispersed knowledge, on the other hand (BATHELT et al, 2004). A global orientation typically is found with innovation intensive firms in advanced stages of development (GEENHUIZEN, 2007). These findings correspond to the industry-life-cycle and the cluster-life-cycle-hypothesis, suggesting that economic activity is more geographically dispersed as the industries mature (SWANN, 1998;AUDRETSCH and FELDMAN, 1996).…”
Section: The Problem Of Lock-inmentioning
confidence: 99%
“…Therefore, it is argued that successful innovation is based on the appropriation of specialized regional know-how, on the one hand, and globally dispersed knowledge, on the other hand (BATHELT et al, 2004). A global orientation typically is found with innovation intensive firms in advanced stages of development (GEENHUIZEN, 2007). These findings correspond to the industry-life-cycle and the cluster-life-cycle-hypothesis, suggesting that economic activity is more geographically dispersed as the industries mature (SWANN, 1998;AUDRETSCH and FELDMAN, 1996).…”
Section: The Problem Of Lock-inmentioning
confidence: 99%
“…rough set analysis and dealing with a small sample of young, high-tech companies in the Netherlands, the study addresses the following questions: (1) which factors are shaping the geographical scale of knowledge networks and to what extent is global knowledge networking in innovation supported by virtualization, and (2) how are changing global knowledge networks affecting local connectedness of companies? Compared with previous work (Van Geenhuizen, 2008aGeenhuizen, , 2008b) more in-depth results have been gained, due to a stronger emphasis on virtualization and on influence of different types of global knowledge relations (MNC context) on local connectedness.…”
Section: In Search Of Knowledge In Open Networkmentioning
confidence: 99%
“…Further, the value of 1.0 for the quality of the core means that the reliability of the classification for the dependent variable and the overall quality of the information table are at their maximum. Source: Adapted from van Geenhuizen (2005van Geenhuizen ( , 2008b …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The new innovation theory (Acs et al, 2002) has clearly demonstrated that innovative and creative firms 2 are key actors in the economic change and transformation process of cities and regions. The interface between the business performance of individual firms and the socio-economic development of cities and regions calls for a thorough analysis of complex spatial systems, with due attention to the dynamic drivers of, and effects on, balanced regional development ( van Geenhuizen, 2007;Kourtit et al, 2011a).…”
Section: The Complex Space-economymentioning
confidence: 99%